KEPATUHAN 5 MOMEN HAND HYGIENE PADA PETUGAS DI LABORATORIUM KLINIK CITO YOGYAKARTA (ACTION RESEARCH) - Pangisti Dwi Ananingsih; Elsye Maria Rosa (Universitas Muhammadiyah Yogyakarta, 2016)
Background: Hospital Associated Infection (HAIs) is still a problem through out the world and in Indonesia. Health officials have a major role in the transmission of these infections. However, the low level of compliance of five moments of hand hygiene among health care workers is still one of the factors that cause high spread of HAIs. To hand let his, it is necessary to counseling about the importance of 5 moments of hand hygiene for health worker towards patient health. Counseling can be done in various models, such as posters, training and simulation. Methods: The study is a qualitative research with action research. Conducted in September 2015 in wards in Clinical Laboratory “Cito” Yogyakarta, population as well as samples in this study were all health care workers in first floor of the Clinical Laboratory Cito Yogyakarta that consisting of nurses, analysts, doctors, radiographers, customer service, and cleaning service. Results and Discussion: The results showed the average rate of compliance of five moments of hand hygiene officer in the Clinical Laboratory Cito Yogyakarta continues to increase after extension, from 0% at the stage of the pretest be at 16,67% after being given counseling using the poster (cycle I) , increased to 32,50% after being given training (cycle II) and increased to 40,83% after being given counseling using simulation (cycle III). The factors that influencing the adherence of 5moments of hand hygiene in Cito Clinical Laboratory are: workload, the fear of hitting by irritant dermatitis, forgotten, lack of motivation, the lack of commitment of the company, lack of knowledge, and access to hand hygiene. Conclusion: 5moments of hand hygiene compliance of the workers increasing after the poster socialitation, training, and simulation. The management is expected to give more attention in improving of5moments of hand hygiene for health worker in Clinical Laboratory Cito Yogyakarta.